Gender differences in reporting workplace violence: a qualitative analysis of administrative records of violent episodes experienced by healthcare workers in a large public Italian hospital - Maria Michela Gianino; Daniela Acquadro Maran; Claudio Giovanni Cortese; Pierluigi Pavanelli; Giulio Fornero (BMJ Open)
Objectives This study aims to analyse, from a descriptive and qualitative point of view, the episodes of violence reported by healthcare workers (HCWs) in a large public Italian hospital. Qualitative analysis permits us to collect the victims’ words used to describe the event and the ways in which they dealt with it. A comparison between genders was performed to better understand what type of different strategies could be used to improve the prevention of workplace violence for HCWs.Design and setting The retrospective observational study was carried out in ‘Città della Salute e della Scienza’, a complex of four interconnected hospitals situated in Northern Italy. This study analysed aggression data from the 4-year period of 2015–2018 that included all HCW categories. The data were obtained from the aggression reporting form.Participants The analysed records were supplied by 396 HCWs (3.6% of all HCWs in the hospital).Results Male HCWs aged <30 years did not report violent episodes that occurred in the workplace, while male HCWs with 6–15 years of work experience reported more violent episodes than their female counterparts. Among the HCW professions, nursing was the profession, in which HCWs were more prone to experience a violent episode, while male medical doctors were more prone to report violent episodes than female medical doctors. Moreover, female HCWs experienced more verbal violence (insults) than male HCWs did, while male HCWs experienced more physical violence (bodily contact) than female HCWs did.Conclusions The findings from this explorative study suggest that there is a gender difference in the characteristics of workplace violence perpetrated by patients, patients’ relatives and visitors and in the way in which these episodes are described. Consequently, it is important for informative and preventive courses to consider gender differences in experiencing a violent episode.